Rationale, current state and opportunities in combining biologic disease modifying antirheumatic drugs in rheumatoid and psoriatic arthritis - Mutlu, Melek Yalcin; Tascilar, Koray; Schett, Georg (Joint Bone Spine, 2023)
The advent of biologic disease modifying antirheumatic drugs (bDMARDs) has considerably improved patient outcomes in inflammatory arthritis. However, not all patients reach the state of remission, as disease can be resistant even to single cytokine inhibition by bDMARDs. Simultaneous or sequential inhibition of multiple cytokines may be considered in situations where disease control is not adequate under singular inhibition of cytokines. Although there have been some disappointing experiences in the past with combination of bDMARDs, the ongoing improvement of our understanding about inflammatory pathways and the overall better safety understanding of bDMARDs seem to make new biologic treatment combinations possible. This review covers the rationale and current evidence for bDMARDs combination in inflammatory arthritis.
CRIS-Team Scopus Importer:2023-06-09
Keywords: Biologicals; Combination therapy; Cytokine blockade; Psoriatic arthritis; Rheumatoid arthritis